Flow investigation around cylinders assembled in a confined straight channel geometry. Issue 1 (May 2021) - Tanase, Nicoleta-Octavia; Broboana, Diana; Balan, Corneliu
Abstract: The paper is dedicated to experimental and numerical investigations of the dynamics of 3D-flow around a cylinder with 10 mm diameter. The cylinder is positioned in a confined geometry represented by a long straight channel with 50 mm width and 10 mm height. The study analyses the dependence on the Re-number of the path lines distributions in the vicinity of the immersed cylinder. The visualized flow patterns are fairly reproduced by the numerical solutions of the Navier-Stokes equations up to Re = 1000. The velocity and wall stresses are computed in the vicinity of the cylinder. One main goal of the present work is established by the correlation between the flow pattern, wake boundary and wall shear stress distributions down-stream the cylinder.